THE USE OF SOCIAL MEDIA AS A LEARNING MEDIA IN IMPROVING STUDENTS’ MOTIVATION IN THE MANAGEMENT ACCOUNTING COURSE - Prihastuti, Asepma Hygi; Wahyuni, Sri; Ramadhani, Suci (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2018)
This study aims to improve students’ motivation in Management Accounting courses by using social media as a learning media in the classroom. The use of social media is inspired by the fact that that most of internet users are 19-34 years old, which is around 49.52% of them access social media more than 3 hours per day (2017 APJII survey). Participants of this study were students of STIE Persada Bunda who took Management Accounting course at the 2018/2019 Academic Year. This study employed Classroom Action Research method with 2 cycles with descriptive analysis. Before using media social as a learning media, the average value of students’ motivation was 60%. In the first cycle it was obtained that an average value of students’ motivation was 71%. It means that student of STIE Persada Bunda motivation was high. The second cycle obtained that an average value of students’ motivation was 82%. This means that motivation of students of STIE Persada Bunda was very high. This study reveals that students’ motivation has been significantly increased. It is expected that learning achievement of students in management accounting course will be increased too.